Banking and industrial finance in India - Das, Nabagopal (Calcutta, 1936)
The present work is an attempt to study the problem of banking and industrial finance in India from a strictly economic standpoint and free from all racial or political bias. The preliminary survey was commenced by me in India, but the major portion of the study was done in London at the School of Economics and Political Science. The subject has first been treated from the historical standpoint. Some interesting facts relating to the history and development of the money market in India have been embodied for the first time in this book and considerable new light has been thrown upon other facts which, though not new, have up till now remained comparatively unknown to the student of Indian economics. On the other hand, in the analytical study which occupies the second half of this book, I have tried to consider the systems of industrial finance in other countries and to judge how far the present economic development of India and the fundamental peculiarities of its money market are conducive to the adoption of methods that are foreign to the tradition of this country. Throughout, I have attempted to maintain a broad and compre hensive outlook and to remember that difficulties of industrial finance are but one of the many handicaps from which industry in India suffers.
Keywords: Economics